Accountability for After-School Care Devising Standards and Measuring Adherence to Them - Beckett, Megan K. (RAND Corporation, 2001)
Increasing numbers of children are participating in after-school programs, and with more federal and state funding the number of such programs is likely to grow. This growth has been occurring, however, with little guidance as to what program features or practices might be most helpful in nurturing the educational achievement, emotional development, and health of the children involved. This book helps fill that need for guidance by offering a set of 18 model practices against which after-school programs can be evaluated. The authors provide ways to score adherence to the criteria, from excellent to inadequate; survey forms for collecting the information to assign these grades; and an illustrative application of their approach to a set of real-world after-school programs.